Flash Floods, Livelihoods and Food Security: Evidence from the Affected Smallholder Farming Households in Northeast Bangladesh (Social Science Review, 2025)
The 2017 flash flood events in Northeast districts created differential impacts on poor people; therefore, the adaptation strategies adopted by the poor were insufficient to survive. The weakness in these strategies often resulted in vulnerability to them. The present paper attempts to argue that the impacts created by those barriers are heterogeneous in nature, which did not receive considerable attention in ongoing research on this issue. This research has been conducted in two villages in the Habiganj district. Purposive sampling methods were used aiming to investigate how poor households adapt to flash flood disasters. A mixed method was applied to capture the scenario, which included a household questionnaire survey, focus group discussions, key informant interviews, and informal discussions. Findings suggest that flood disasters affect farming households differently. As the findings reveal that the agriculture-based livelihoods are affected by the flash flood drastically that created household food insecurity in many smallholder farming households. The findings present some specific policy suggestions for policymakers and development workers to shape policies that may benefit all actors more inclusively.Social Science Review, Vol. 41(1), June 2024, Page 57-72.